Fabric of consolidated kaolinite / by R. Torrence Martin, Charles C. Ladd. - Ladd, Charles C. (Charles Cushing); United States. Army Materiel Command.; U.S. Army Engineer Waterways Experiment Station.; Massachusetts Institute of Technology. Soil Mechanics Division.; Martin, Robert T. (Tufts University. Tisch Library., 2019)
1 online resource (73 pages) : illustrations.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.